Age-Related Hearing Loss Is Accompanied by Chronic Inflammation in the Cochlea and the Cochlear Nucleus - Seicol, Benjamin J.; Lin, Shengyin; Xie, Ruili (Frontiers in Aging Neuroscience, 2022)
Age-related hearing loss (ARHL) is a major hearing impairment characterized by pathological changes in both the peripheral and central auditory systems. Low grade inflammation was observed in the cochlea of deceased human subjects with ARHL and animal models of early onset ARHL, which suggest that inflammation contributes to the development of ARHL. However, it remains elusive how chronic inflammation progresses during normal aging in the cochlea, and especially the accompanying changes of neuroinflammation in the central auditory system. To address this, we investigated chronic inflammation in both the cochlea and the cochlear nucleus (CN) of CBA/CaJ mice, an inbred mouse strain that undergoes normal aging and develops human-like late onset ARHL. Using immunohistochemistry, confocal microscopy, and quantitative image processing, we measured the accumulation and activation of macrophages in the cochlea and microglia in the CN using their shared markers: ionized calcium binding adaptor molecule 1 (Iba1) and CD68—a marker of phagocytic activity. We found progressive increases in the area covered by Iba1-labeled macrophages and enhanced CD68 staining in the osseous spiral lamina of the cochlea that correlated with elevated ABR threshold across the lifespan. During the process, we further identified significant increases in microglial activation and C1q deposition in the CN, indicating increased neuroinflammation and complement activation in the central auditory system. Our study suggests that during normal aging, chronic inflammation occurs in both the periphery and the central auditory system, which may contribute in coordination to the development of ARHL.